Development of LCD/SLM driver IC/FPGA - Tan, John Chin Liang (2015)
In this report, the project is based on a platform that is capable of interfacing the information transmitted from a personal computer and Field Programmable Gate Array (FPGA) via Universal Serial Bus (USB) link and it is to be displayed on a LCD display screen. This platform aims to serve the purpose of converting information sent from the personal computer to the LCD display screen to display the image or information via a FPGA prototype board at the data link transmission speed which can be as quick as 60 Hertz. The platform which consist of both the USB medium and FPGA development board establishes the data link connection and it can be implemented on different type of display screens through adaptation with the given data sheet information. For ease of generating the image information to be transmitted to the display screen, a Graphical User Interface (GUI) is implemented on the personal computer and it is used to communicate to the FPGA development board via USB medium. This project is suitable for display applications which require high speed operation displays.